SITUATION OF REGULATIONS FOR HOLDING COMPANIES IN ROMANIA - Braga, Viorica Filofteia; NAFTANAILA, Cristina Alina; AVRAM, Laurentia (Annals of Spiru Haret University. Economic Series, 2016)
In this article we present the tax facilities applicable to Romania on holding companies, ranking of the first 20 countries that investing in our country, their activities field and the necessity to approve the law holding company.